2020
DOI: 10.3390/pr8091175
|View full text |Cite
|
Sign up to set email alerts
|

Phytotoxicity and Effect of Ionic Liquids on Antioxidant Parameters in Spring Barley Seedlings: The Impact of Exposure Time

Abstract: The influence of the ionic liquids (ILs) tetrabutylammonium bromide [TBA][Br], 1-butyl-3-methylimidazole bromide [BMIM][Br], and tetrabutylphosphonium bromide [TBP][Br] added at different concentrations to the soil were studied for the growth and development of spring barley seedlings. Samples were harvested at three different time points: day 7, 14, and 21 after addition of ILs. The results show that [TBP][Br] was the most toxic. The introduction of this IL at the dose of 100 mg kg−1 of soil DM decreased the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Biczak et al . (2020) also detected the activities of SOD and other enzymes in spring barley seedlings, with a SOD activity of 37.80 U g −1 , significantly lower than that of BGP.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Biczak et al . (2020) also detected the activities of SOD and other enzymes in spring barley seedlings, with a SOD activity of 37.80 U g −1 , significantly lower than that of BGP.…”
Section: Resultsmentioning
confidence: 99%
“…The measurement results showed that the SOD activity of BGP was 94.73 AE 21.06 U g À1 . Biczak et al (2020) also detected the activities of SOD and other enzymes in spring barley seedlings, with a SOD activity of 37.80 U g À1 , significantly lower than that of BGP.…”
Section: Tfc In Bgpmentioning
confidence: 93%
“…Therefore, the presence of contaminants, including ionic liquids, in the soil can affect its growth and development [ 28 ]. The results of [TBP][Br] phytotoxicity for spring barley are described in another article [ 29 ]. Moreover, spring barley is indicated in Polish norm PN-EN ISO 11269-2 [ 30 ] as a recommended species for xenobiotic toxicity testing.…”
Section: Introductionmentioning
confidence: 99%